Serum and glucocorticoid inducible protein kinases (SGKs): a potential target for cancer intervention - Rajesh Basnet; Grace Qun Gong; Chenyao Li; Ming-Wei Wang (Elsevier, 2018)
The serum and glucocorticoid inducible protein kinase (SGK) family members share similar structure, substrate specificity and function with AKT and signal downstream of the phosphatidylinositol 3-kinase (PI3K) signalling pathway. They regulate a range of fundamental cellular processes such as cell proliferation and survival, thereby playing an important role in cancer development. This perspective intends to give an overview on the involvement of SGKs (particularly SGK3) in cancer progression, and compares the actions of SGK3 and AKT in cell cycle regulation, oncogenic signalling, and the potential as a therapeutic target for cancer. KEY WORDS: SGK, AKT, PI3K, Cancer, Signalling, Kinase, Inhibitor